2017
DOI: 10.3171/2016.11.spine16746
|View full text |Cite
|
Sign up to set email alerts
|

Long-term clinical and radiographic outcomes of the Prestige LP artificial cervical disc replacement at 2 levels: results from a prospective randomized controlled clinical trial

Abstract: OBJECTIVEThe aim of this study was to assess long-term clinical safety and effectiveness in patients undergoing anterior cervical surgery using the Prestige LP artificial disc replacement (ADR) prosthesis to treat degenerative cervical spine disease at 2 adjacent levels compared with anterior cervical discectomy and fusion (ACDF).METHODSA prospective, randomized, controlled, multicenter FDA-approved clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
46
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(49 citation statements)
references
References 22 publications
2
46
1
Order By: Relevance
“…The specific methods and procedures for this clinical trial have been described in detail elsewhere, including inclusion and exclusion criteria and detailed definitions of all outcome measures. 11,15 Key components of the research protocol are summarized below.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The specific methods and procedures for this clinical trial have been described in detail elsewhere, including inclusion and exclusion criteria and detailed definitions of all outcome measures. 11,15 Key components of the research protocol are summarized below.…”
Section: Methodsmentioning
confidence: 99%
“…A postapproval study (PAS) with patient follow-up to 10 years was required by the FDA, and 7-year follow-up results have been reported. 15 Those results continued to show the noninferiority of CDA compared to ACDF as well as superiority in overall success and other measures.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…Neurological success was reported in six studies [16][17][18][19][20][21] that comprised 944 patients in the CDA group and 747 patients in the ACDF group. The pooled results indicated that the neurological success rate in the CDA group was significantly higher than that in the ACDF group (OR = 1.54, 95% confidence interval [CI]: 1.14-2.08, p = 0.004) with moderate heterogeneity (I 2 = 34.0%, p = 0.18) ( Fig.…”
Section: Meta-analysis Outcomementioning
confidence: 99%
“…A total of 814 studies were removed because they were duplicates, 1076 studies were excluded based on their titles and abstracts, and 43 studies were excluded for other reasons. As a result, 21 studies were included for further evaluation. Among them, 2 studies were partial results of multicenter RCT and 8 studies included duplicated data for publication.…”
Section: Resultsmentioning
confidence: 99%